Pengaruh Pembinaan Mental Keagamaan Terhadap Prajurit TNI Kosek Hanudnas III Medan Polonia - Lenda Jurmiana (UIN Sumatera Utara, 2021)
This study talks about the religious mental development of the TNI at Soewondo Airfield in Medan, Polonia. To create members who are weighty or classy, both themselves and their religion are formed religious mental formation structures. With this bintal activity in order to further enhance the personality that is better in terms of attitude and behavior. The creation of coaching is because many soldiers do not control their emotions in carrying out their duties because Soldiers are trained in very harsh and disciplined conditions. With this study, the authors conducted a qualitative research approach, namely research conducted directly on the subject under study, to obtain data on the problem. Soewondo Air Base's religious mental development program is a means of forming a soldier's identity so that he has a healthy mentality and upholds Islamic teachings so that he can become a role model for soldiers and society. The results showed that the form of mental religious development at the Hanudnas III boarding school in Medan that studying is the most compulsory thing that is done by every human being, because studying is a form of worship as the Prophet Muhammad SAW said. This method is carried out through routine recitation activities, yasin, tahlil, warning Islamic holidays and so on. Supporting factors in the effort to develop mental religion are the religious spirit of the TNI members themselves, the harmony of life between religious communities around the headquarters and the disciplined military environment, while the inhibiting factor is the differences in character or personality between TNI members.